EDUCATIONAL OUTREACH TO PREVENT AND COMBAT BULLYING ON SOCIAL MEDIA FOR PRIMARY SCHOOL STUDENTS - Ulum, Bachrul; Rahayu, Dwi Agustina; Astutik, Leny Suryaning; Eka Putra, AA Putu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aims to enhance the knowledge and skills of elementary school students in preventing and addressing bullying, particularly cyberbullying. The activity was conducted at SDN 1 Beji, Boyolangu, Tulungagung, involving students from grades 1 to 6. The implementation methods included an initial observation to identify students’ conditions and needs, educational counseling using an interactive approach, and an evaluation through questionnaires to measure students’ understanding and behavioral changes. The results show a significant improvement in students’ comprehension of bullying concepts and their ability to identify various forms of bullying. In addition, the program encouraged a behavioral shift among students, from previously acting only as bystanders to becoming more proactive in reporting bullying incidents and offering support to victims. Overall, this program proved effective in creating a safer school environment and increasing students’ awareness of the importance of bullying prevention.